Characteristics and Influencing Factors of Real-Life Violence Exposure Among Chinese College Students - Wang, Weiling; Wang, Yuping; Qian, Yuyan; Yu, Yuanfang (Frontiers in Psychology, 2020)
This study aimed to explore the characteristics and influencing factors of violence exposure in real life among Chinese college students. A sample of 375 college students was randomly selected to complete three questionnaires. The results indicated that participants had higher scores as victims and witnesses on violence exposure in community than they did in family. Male students had higher scores than females in both family and community violence exposure. Subjects with lower father’s education level scored significantly higher than others in family violence exposure by victimization and community violence exposure by witnessing and victimization. Participants growing up in rural areas had significantly higher scores than others in family violence exposure by victimization and community violence exposure by witnessing. Finally, those subjects with siblings reported higher scores than those from only child families in family violence exposure by witnessing. Multiple regression analysis showed that deviant behaviors of peers, gender, and single-child status were significant influencing factors of respondent violence exposure. More efforts should be taken to effectively cope with existing violence exposure in college students and minimize the potential of future exposure.